Correlation between cucumber genotype and resistance to damping-off disease caused by Phytophthora melonis. Issue 1 (1st January 2019) - Hashemi, Lida; Golparvar, Ahmad Reza; Nasr Esfahani, Mehdi; Golabadi, Maryam
Abstract: Cucumber ( Cucumis sativus L.) damping-off disease caused by Phytophthora melonis is a limiting factor affecting cucurbit production. This study assessed a collection of 38 domestic and exotic commercial cucumber genotypes for damping-off resistance at transplanting and 50% flowering. Plants were classified using a four-score scale, the average damping-off percentage ranging from 7.92% (resistant) to 88.01% [highly susceptible (HS)]. Most of the genotypes were susceptible and HS to P. melonis . These genotypes were analyzed with 15 inter-simple sequence repeat (ISSR) markers. A total of 317 bands were produced, of which 297 bands (93.69%) were polymorphic. The primer ISSR29 possessed the highest resolving power, polymorphic information content and marker index value, which could be the most informative primer for distinguishing cucumber genotypes. Cluster analysis and principal component analysis were carried out and there was a probable connection between cucumber genotypes and resistance level against P. melonis, indicating possible application for ISSR in studying disease resistance of cucumber and producing cultivars that resist damping-off. The expression of three candidate genes probably involved in the defence against P. melonis was quantified by quantitative real-time polymerase chain reaction in five cucumber genotypes showing different susceptibility to the pathogen. CsWRKY20, CsLecRK6.1 and LOX1 genes were differentially expressed depending on genotype in early stages of infection. LOX1 was the most expressed gene across experiments and the one that best discriminated between susceptible and resistant genotypes. These results are a valuable resource for future functional genomics studies to unravel the molecular mechanisms of C. sativus/P. melonis interaction.